A theoretical framework for digital learning spaces: learning in individual spaces, working groups, communities of interest, and open connections - Christian Dalsgaard; Thomas Ryberg (Association for Learning Technology, 2023)
The paper presents a theoretical framework of four digital learning spaces: Individual space, Working group, Community of interest, and Open connections. The theoretical framework aims to highlight the unique potentials of digital technologies to expand learning activities. More specifically, the framework contributes with descriptions of specific learning activities that highlight the learning potentials of different social forms as well as learning potentials of digital technologies. The paper highlights learning potentials of digital technologies within each learning space; digital technologies as cognitive partners, collaboration tools, sharing tools, and as network relations and network effects. The framework is developed on the shoulders of existing educational frameworks, and contributes to learning technology research by combining conceptions of social forms, learning theory, and digital technology studies. Further, the framework is directed towards educational practice as a tool to develop learning activities, and to design digital learning spaces. The framework intends to function as a guiding framework that can help teachers and developers to focus on different levels of learning spaces and specific learning activities. Finally, the paper argues that digital technologies have the potential to expand opportunities for learning: specifically, to expand individual agency (within the individual space), collaborative knowledge building (within the working group), transparency (within a community of interest), and interaction with the outside world (through open connections).